Structural Optimization of an Aeroelastically Tailored Composite Flat Plate Made of Woven Fiberglass/Epoxy - Attaran, A.; Majid, D. L.; Basri, S.; Mohd. Rafie, A. S. (2006)
Effects of aspect ratio, sweep angle, and stacking sequence of laminated composites were studied to find the optimized configuration of an aeroelastically tailored composite wing idealized as a flat plate in terms of flutter speed. The aeroelastic analysis has been carried out in frequency-domain. The 2D finite element analysis in conjunction with Doublet-lattice Method (DLM) has been opted for structural and unsteady aerodynamic analysis, respectively. The interpolation between aerodynamic boxes and structural nodes has been done using surface spline. To study the effect of stacking sequence the classical lamination theory (CLT) has been chosen. All the analyses have been implemented in MSC.NASTRAN/PATRAN. The parametric studies showed the effective ply orientation angle to be somewhere between 15 and 30 degree, while the plates with lower aspect ratio seems to have higher flutter speed. Forward swept configurations show higher flutter speed, yet imposed by divergence constraint.